Monkeypox Represents Re-Emerging Zoonotic Disease: Review - Ozdan Akram Ghareeb; Awni Ismail Sultan (Scholars Digest Publishing, 2023)
One of the major public health disasters is the re-emerge of monkeypox (MPX) infection. This disease was considered emerging zoonotic that affects humans as well as animals, including monkeys. The re-emergence of zoonotic diseases with little documentation has led to dispersal of inaccurate facts. Therefore, the aim of this review is to summarize important issues about this infection. The genome of MPX virus is double-stranded DNA. Rodents are the likely source of infection, along with monkeys, porcupines, and sun squirrels actively contributing to the transmission of this contagion. In general, humans’ infection occurs by direct contact with infected animals through the contents of the skin lesion, as well as body secretions. After the virus enters the host, it multiplies at the site of infection, penetrating the lymph nodes. Symptoms are characterized by fever, lymphadenopathy, and high rate of lesions in genitals, perianal, and oral regions. In order to achieve prevention, the smallpox vaccine must be used, especially for frontline workers who are most vulnerable to infection, with an emphasis on implementing the principles of one health to control the non-reemerging of this infection.